Multiphase development and evaluation of cognitively diagnostic assessment and adaptive intervention for tracking learning - Tenorio, Alvin Daiz
To contribute to the limited body of knowledge on the methodological and analytical procedures in the application of the longitudinal Cognitive Diagnosis Models (CDMs), this study was conducted to develop and evaluate cognitively diagnostic assessment and adaptive intervention for tracking learning trajectories in fraction addition and subtraction. A recursive multiphase mixed methods learning tracking was employed as the overarching design that subsumed the sub-designs in each of the five phases of the study, namely (1) cognitive model development, (2) cognitively diagnostic assessment development, (3) attribute mastery and non-mastery diagnosis, (4) adaptive intervention development and implementation, and (5) tracking learning trajectories. Results showed that the cognitive model that can describe students’ mastery of fraction addition and subtraction tasks consists of seven attributes. These attributes were measured using the developed Cognitively Diagnostic Fraction Addition and Subtraction Test (CDFAST), a 30-item test consisting of items that measure a single or combination of identified attributes. The subsequent attribute mastery and non-mastery diagnosis performed showed that most of the respondents had a limited number of mastered attributes crucial for performing fraction addition and subtraction. With this, an adaptive intervention targeting the unmastered attributes of the respondents was developed and was called Fraction DRIVE. This intervention was given to the experimental group, while the comparison group was given a separate set of instructions. The analysis of the learning trajectories of the respondents showed the effectiveness of the intervention at the group-level growth for the experimental group and at the individual-level growth for the comparison group. The lessons gained from the implementation of the longitudinal CDM showed the intricacy and complexity of the procedure, but they provided insights as to its plausibility in tracking the learning trajectories of students not only in the context of fraction addition and subtraction but also in other domains.